If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 63 = 25x Solving 63 = 25x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25x' to each side of the equation. 63 + -25x = 25x + -25x Combine like terms: 25x + -25x = 0 63 + -25x = 0 Add '-63' to each side of the equation. 63 + -63 + -25x = 0 + -63 Combine like terms: 63 + -63 = 0 0 + -25x = 0 + -63 -25x = 0 + -63 Combine like terms: 0 + -63 = -63 -25x = -63 Divide each side by '-25'. x = 2.52 Simplifying x = 2.52
| -28x^2-32x+16=0 | | -x^2+4.5x+1=0 | | 5/1=16/x | | x^2=420 | | 2(k+7)=32 | | 2x+5x-10+3=6x-7.2+x | | 4A=(B+b)*h | | 4x^3+8x^2+5x=0 | | -8x-2x=-56+48 | | 60=3.5x-0.05x^2 | | 5x-3(2x-9)=28 | | 1x=7x+42 | | 39=4x+5 | | 3x+x(2+2)+10=5(x^2+2)-3(x^2-1) | | 1x+0.4x=1 | | 2n4=6/9 | | √36x^2/4x^6 | | X+27-14=-15 | | 6x^2-1=2 | | 8x-(4+5x)=17 | | 7x-5(5x+8)=11+8(5-4x) | | c(m)=0.15+0.75 | | 8x-6=8x+20 | | (2x+11)=(10x-17) | | 144x^2+732x-36=0 | | 3(4r-7)-4(r-3)= | | 4-2(x-5)=1 | | 7c+3=4c+21 | | 16/128=24/x | | 13x+4y=7 | | 5p+4=19 | | 2(p+3)=3 |